Activity of D-carnitine and its derivatives on Trypanosoma infections in rats and mice - Manganaro M.; Mascellino M.T.; Gradoni L. (Parasite, 2003)
Little progress has been made in the treatment of African trypanosomiasis over the past decades. L-carnitine has a major role in glycolysis-based energy supply of blood trypanosomes for it stimulates constant ATP production. To investigate whether administration of the isomer D-carnitine could exert a competitive inhibition on the metabolic pathway of the L-form, possibily resulting in parasite replication inhibition, several formulations of this compound were tested on Trypanosoma lewisi and T. brucei rhodesiense in rodent models. High oral dosages of D-carnitine inner salt and proprionyl-D-carnitine were not toxic to animals and induced about 50 % parasite growth inhibition in reversible, i.e. competitive, fashion. A putative mechanism could be an interference in pyruvate kinase activity and hence ATP production. Considering both, lack of toxicity and inhibitory activity, D-carnitine may have a role in the treatment of African trypanosomiasis, in association with available trypanocidal drugs.